A STUDY TO ASSESS THE KNOWLEDGE ON HOME MANAGEMENT OF DRY COUGH AMONG MOTHERS OF UNDER FIVE YEAR CHILDREN IN SELECTED RURAL AREA, SHIVRAJPUR, KANPUR (International Journal of Food and Nutritional Sciences, 2022)
Cough is common in children, especially when they are preschool age. Home management has long been used for dry cough such ashoney, ginger, warm water, and coriander powder with milk. These are effective remedies for dry cough in under five year children. To assess the level of knowledge about home management of dry cough among mothers of under five year children in rural area, Shivrajpur, Kanpur. Non experimental descriptive design was used